Capacidades dinâmicas e as estratégias de internacionalização de vinícolas brasileiras - Tripoli, Angela Cristina Kochinski (2019)
The aim of this research was to identify a relationship between Dynamic Capabilities and internationalization strategies of Brazilian wineries. Through quantitative research carried out with wineries, as members of the Wines of Brazil project, which is the main internationalization agent at this sector, it was possible to identify dynamic exports, strategies, and performance of the wineries internationalization processes. Additionally, a qualitative step was performed to deepen the results, which were found in the quantitative part. The main results were: the number of wineries with international actions is very limited and concentrated in table wines and sparkling wines. On the part of fine wines, they do not have the capacity and interest of competitors, due to the characteristics of the international wine industry being extremely fractional, which emphasizes how local characteristics such as grape variety and terroir. Therefore, basic internationalization strategies are limited to the early, direct and indirect stages. In cases of successful exportations, it was possible to identify two main applications: cooperation; coordination and skills to use the new knowledge acquired.